Geopolymers for Eco-Architecture. Integrated approaches for green strategies activation - Raffaella Aversa; Rossella Franchino; Caterina Frettoloso; Nicola Pisacane; Laura Ricciotti (Agathón)
The construction industry is responsible for 30% of energy consumption, 40% of CO2 emissions, and 50% of raw material extraction. Introducing actions to improve the sustainability of induced impacts is urgently necessary, and it is essential to bring about this change by using innovative materials with a natural matrix and construction processes that optimise the raw materials and allow their recyclability. The article introduces the first outcomes of an interdisciplinary research project focused on applying geopolymers for building components. The research highlights the strategic role of sustainability combined with digitisation in order to improve ecological-environmental performance.